Microbial ecology and biogeochemistry of continental Antarctic soils - Cowan, Don A.; Makhalanyane, Thulani P.; Dennis, Paul G.; Hopkins, David W. (Frontiers in Microbiology, 2014)
The Antarctica Dry Valleys are regarded as the coldest hyperarid desert system on Earth. While a wide variety of environmental stressors including very low minimum temperatures, frequent freeze-thaw cycles and low water availability impose severe limitations to life, suitable niches for abundant microbial colonization exist. Antarctic desert soils contain much higher levels of microbial diversity than previously thought. Edaphic niches, including cryptic and refuge habitats, microbial mats and permafrost soils all harbour microbial communities which drive key biogeochemical cycling processes. For example, lithobionts (hypoliths and endoliths) possess a genetic capacity for nitrogen and carbon cycling, polymer degradation and other system processes. Nitrogen fixation rates of hypoliths, as assessed through acetylene reduction assays, suggest that these communities are a significant input source for nitrogen into these oligotrophic soils. Here we review aspects of microbial diversity in Antarctic soils with an emphasis on functionality and capacity. We assess current knowledge regarding adaptations to Antarctic soil environments and highlight the current threats to Antarctic desert soil communities.